Characterization of buoyant flow stratification behaviors by Richardson (Froude) number in a tunnel fire with complex combination of longitudinal ventilation and ceiling extraction. (5th January 2017) - Tang, F.; Li, L.J.; Dong, M.S.; Wang, Q.; Mei, F.Z.; Hu, L.H.
Highlights: Thermal buoyant flow stratification was investigated in a 72 m long model tunnel. Buoyant flow stratification with ceiling extraction are considered. The smoke flow patterns can be divided into three regimes. Abstract: A series of experiments were carried out in a model-scale tunnel [72 m (length) × 1.5 m (width) × 1.3 m (height)] to investigate the buoyant flow stratification behaviors in a tunnel fire with complexity of combination of longitudinal ventilation and ceiling extraction, which had not been studied before. The horizontal traveling velocity and vertical temperature profile were measured. The buoyant flow stratification conditions were visualized by a laser-sheet, as well as determined objectively by the vertical temperature profile measured. Buoyancy and inertial force are the two important factors influencing the buoyancy stratification. The interaction between them can be expressed by the Froude number or Richardson number. It was found that the buoyant stratification pattern was divided into three regimes. At regime I ( Ri  > 2.0 or Fr  < 0.66), the buoyant stratification was stable and with a clear interface between the upper buoyant flow layer and the lower air layer. At regime II (1.4 <  Ri   <  2.0 or 0.66 <  Fr   <  0.8), the buoyant stratification was basically stable, but some vortexes existed at the interface. At regime III ( Ri  < 1.4 or Fr  > 0.8), a strong mixing existed between the upper buoyant flow and the lower air flow, that the buoyant flow stratification became unstable.